Comparison of mechanical characteristics of different types of shales in the Ordos Basin - Dou, Liangbin; Chen, Jingyang; Zuo, Xiongdi; Liu, Yonghui; Sun, Lin; Fang, Yong; Cheng, Xuebin; Wang, Ting (Frontiers in Earth Science, 2023)
Shale gas is a very important unconventional energy. The mechanical properties of the three types of shale (laminated shale, sandwich shale and foliated shale) are different, and the difference in fracturing effectiveness is very significant. In this paper, the mineral composition, mechanical properties and conductivity of these three different types of shale were studied and compared by X-ray diffraction, triaxial mechanical experiments, and fracture conduction experiments. The study found that the foliated shale has the lowest content of rigid minerals (47.5%), lower elastic modulus and tensile strength (26.98 Gpa and 168.29 MPa, respectively), higher Poisson’s ratio (0.25), the smallest brittleness index (0.48), and larger fracture toughness (0.42). The laminated shale has a higher content of rigid minerals (68.50%), the lowest elastic modulus and tensile strength (25.77 Gpa and 122.46 MPa, respectively), the highest Poisson’s ratio (0.26), the highest brittleness index (0.56), and the lowest fracture toughness (0.18). The sandwich shale has the highest rigid mineral content (78.16%), the highest elastic modulus and tensile strength (35.31 Gpa and 197.37 MPa, respectively), the lowest Poisson’s ratio (0.24), a larger brittleness index (0.52), and larger fracture toughness (0.415). Furthermore, with the increase in the coring angle, the elastic modulus of all three shales increases. In addition, with the increase in closing pressure and the decrease in the sand laying concentration, the proppant embedding depth gradually increases and the conductivity decreases. This means that from the perspective of forming complex fracture networks, the fracturing effect of the foliated shale is unsatisfactory, while the fracturing effect of the laminated and sandwich shales is better. Moreover, it is recommended to prefer directional injection along vertical laminae or at high angles, which is conducive to the formation of complex fracture networks. For laminated shale with low strength, the sand laying concentration should be increased to ensure the conductivity of the fractured fracture. This study provides some technical guidance for the identification of different types of shale fracturing desserts and fracturing processes.